Relationship of serum interleukin-6 and cognitive functions in patients with schizophrenia, a case–control study. Issue 4 (October 2017) - Abdel Mohsen, Mohamed Yousry; Sabry, Noha; Zyada, Fadia; Abdel Samie, Mai; Baz, Heba N.
Abstract : Background: Interleukin-6 (IL-6) is assumed to play a role in the emergence of cognitive deficits in schizophrenia. Aim: The aim of this work was to assess cognitive functions in the domains of working memory, executive functions, psychomotor speed, and sustained attention in patients with schizophrenia and to determine its relationship to serum levels of IL-6. Methods: Forty patients with schizophrenia recruited from the Kasr Al-Ainy psychiatric outpatient clinic and forty healthy controls matched in age, sex, and educational level to the patients' group were assessed and compared as regards the level of serum IL-6. Cognitive functions were assessed using letter cancellation test, digit symbol coding test, digit span, visual memory span, and Wisconsin card sorting test. Results: The mean level of serum IL-6 of the patients with schizophrenia was significantly higher than that of the control group. Patients showed poorer performance in all cognitive tests. There was a statistically significant negative correlation between the level of serum IL-6 and visual memory span backward score. Conclusion: Patients with schizophrenia have higher levels of serum IL-6. They show poorer cognitive performance in the domains of sustained attention, verbal and visual working memory, processing speed and executive functions, and visual memory deficits. There is a correlation between serum IL-6 and visual memory deficits in patients with schizophrenia.